CHALLENGES EXPERIENCED WHILE PROVIDING HOME BASED CARE: A COMMUNITY ORGANISATION'S EXPERIENCE - Erasmus, Charlene (Journal of Community and Health Sciences, 2020)
The large and ever-growing number of people being infected with HIV/AIDS, led to health professionals being unable to cope with these increasing numbers. To combat this challenge, an alternative strategy such as home based care needed to be implemented. When attempting to attend to this need, a deeper understanding of the challenges facing community organizations when providing home based care is necessary in order to formulate these effective and relevant care services. The aim of the study was to explore the challenges faced by Umtha Welanga Community Organization in the provision of HIV/AIDS home based care. A case study using a qualitative approach with in-depth interviews as the data collectionmethod was used. The Umtha Welanga Community Organization constituted the total population therefore no sampling was applied. All the members of the management team and all the home-based caregivers were interviewed. Informed consent as well as consent for recording interview was obtained prior to data collection. Respondents were informed that participation is voluntary and that they can withdrew at any time. Data analysis began immediately after completion of all the interviews by transcribing and translating the audio-taped data. Thematic analysis was used in which data was coded and categorized. The main areas of concern were gender inequality, insufficient funding, lack of disclosure and trust, risk faced by caregivers and lack of recognition Finances appear to be, both for the organization and the home-based carers, a specifically influential obstacle in the implementation and maintenance of the services. Lack of recognition by the government and lack of trust and disclosure towards care workers; create difficult conditions for them to perform their tasks and duties. Care services also present risks and dangers to caregivers such as being susceptible to criminal activity, feeling unsafe and vulnerable.